TCR gene segment usage and HLA alleles that are associated with cancer survival rates also represent racial disparities. (30th December 2022) - Angelakakis, George; Serraneau, Karisa S.; Barker, Vayda R.; Callahan, Blake M.; Tong, Wei Lue; Zaman, Saif; Huda, Taha I.; Blanck, George
Abstract: Understanding racial disparities in cancer outcomes continues to be a challenge, with likely many factors at play, including socioeconomic factors and genetic polymorphisms impacting basic cellular and molecular functions. Additionally, it is possible that specific combinations of environment and genetics have specific impacts. T‐cell receptor (TCR) gene segment usage, HLA allele combinations have been associated with autoimmune and infectious disease courses, and more recently, TCR gene segment usage, HLA allele combinations have been associated with distinct survival outcomes in cancer as well. We examined several such, previously reported cancer‐related TCR gene segment usage, HLA allele combinations for evidence of racial disparities, with regard to the prevalence of the combination in different racial groups. Results indicated that TCR gene segment usage, potentially reflecting environmental factors related to previous pathogen exposure, in combination with certain HLA alleles or independently, may represent a novel explanation for racial disparities in cancer outcomes. Overall, at this point, a genetic connection to racial disparities in cancer outcomes is detectable but remains modest, suggesting that other factors, such as socioeconomic factors, remain as important considerations.